Maternal outcomes of term breech presentation delivery: impact of successful external cephalic version in a nationwide sample of delivery admissions in the United States. Issue 1 (December 2016) - Weiniger, Carolyn; Lyell, Deirdre; Tsen, Lawrence; Butwick, Alexander; Shachar, BatZion; Callaghan, William; Creanga, Andreea; Bateman, Brian
Abstract Background We aimed to define the frequency and predictors of successful external cephalic version in a nationally-representative cohort of women with breech presentations and to compare maternal outcomes associated with successful external cephalic version versus persistent breech presentation. Methods Using the Nationwide Inpatient Sample, a United States healthcare utilization database, we identified delivery admissions between 1998 and 2011 for women who had successful external cephalic version or persistent breech presentation (including unsuccessful or no external cephalic version attempt) at term. Multivariable logistic regression identified patient and hospital-level factors associated with successful external cephalic version. Maternal outcomes were compared between women who had successful external cephalic version versus persistent breech. Results Our study cohort comprised 1, 079, 576 delivery admissions with breech presentation; 56, 409 (5.2 %) women underwent successful external cephalic version and 1, 023, 167 (94.8 %) women had persistent breech presentation at the time of delivery. The rate of cesarean delivery was lower among women who had successful external cephalic version compared to those with persistent breech (20.2 % vs. 94.9 %;p  < 0.001). Compared to women with persistent breech at the time of delivery, women with successful external cephalic version were also less likely to experience several measures of significant maternal morbidity including endometritis (adjusted Odds Ratio (aOR) = 0.36, 95 % Confidence Interval (CI) 0.24–0.52), sepsis (aOR = 0.35, 95 % CI 0.24–0.51) and length of stay > 7 days (aOR = 0.53, 95 % CI 0.40–0.70), but had a higher risk of chorioamnionitis (aOR = 1.83, 95 % CI 1.54–2.17). Conclusions Overall a low proportion of women with breech presentation undergo successful external cephalic version, and it is associated with significant reduction in the frequency of cesarean delivery and a number of measures of maternal morbidity. Increased external cephalic version use may be an important approach to mitigate the high rate of cesarean delivery observed in the United States.